Les pratiques de bénévoles auprès d’enfants migrants en difficulté scolaire : un système d’activité sous tension - Nathalie Muller Mirza; Oriane Albanèse (Recherches en Éducation)
Volunteering is a dynamic area of activity in European societies and plays an important role, particularly for vulnerable groups. In this respect, it occupies a place both on the margins and in interaction with state authorities, and is at the heart of tensions between paid work and self-giving. In this article, we present the results of a study that aimed to better understand "voluntary work" from the point of view of the actors: How do individuals give meaning to work that is generally presented as little prescribed? What kind of "real" activity do they carry out? The study concerned volunteers working in a collectivity in a town situated in the French-speaking part of Switzerland, oriented towards providing school support to children from migrant backgrounds who have difficulties at school. By articulating singular and collective logics, following a sociocultural approach, we examine the way in which individuals involved carry out the concrete practices that constitute their "work" and how they translate the constraints of the different systems of activity in which they take place. Based on the analysis of interviews, we show that the practices of volunteers are at the heart of tensions that arise from both identity and political issues.